ADAB AHLUL QUR’AN PERSPEKTIF IMAM NAWAWI : Analytic Study of the Book of At-Tibyan Fi Adabi Hamalatil Qur'an - budi suhartawan; Muizzatul Hasanah (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
The Qur'an is the book of the best morals and adab of all time. The ultimate miracle, the noblest reading, a manual that will guide us in our daily life until the end of the world. Imam Nawawi is a pious and pious scholar, he is also referred to as a scholar who is very productive in terms of writing. So it is not surprising that his works are numerous, popular, printed continuously and used as the main source in religious studies (Islamic studies). One of his works is the Book of Tibyan Fii Adabi Hamalatil Qur'an as the main reference in this research. This paper aims to reveal how Adab Ahlu Al-Qur'an is from Imam Nawawi's perspective and how Imam Nawawi narrates the contents of his book. This research is included in library research (library research). With data collection techniques using documentation studies of books and texts from the Book of Tibyan Fii Adabi Hamalatil Qur'an and content analysis. It turns out that as a whole the book talks about the manners and morals of a teacher, student, lover and practitioner of the Qur'an (ahlul qur’an). Imam Nawawi's perspective between teachers and students must have adab and morals when interacting with the Qur'an. The contents of the book include: the virtue of reading and memorizing it, the virtue of qira’ah and ahlul qira’ah, the obligation to glorify the ahlul qur'an, adab for teachers, students, and memorizing of the Qur'an, adab of reading the Qur'an, adab towards the Al-Qur'an 'an, recommendations for reading verses and letters at certain times, writing and ennobling the Al-Qur'an mushaf.